The effects of an oral preparation containing hyaluronic acid (Oralvisc®) on obese knee osteoarthritis patients determined by pain, function, bradykinin, leptin, inflammatory cytokines, and heavy water analyses - Nelson, F. R.; Zvirbulis, R. A.; Zonca, B.; Li, K. W.; Turner, S. M.; Pasierb, M.; Wilton, P.; Martinez-Puig, D.; Wu, W. (Rheumatology international, 2015)
The purpose of this study was to determine the effects of an oral preparation containing hyaluronic acid on osteoarthritic knee joint pain and function as well as changes in inflammatory cytokines, bradykinin, and leptin. We also used heavy water to determine the turnover rates of glycosaminoglycans in synovial fluid. This was a double-blind, randomized, placebo-controlled study of 40 subjects over a period of 3 months. Visual analog scale, Western Ontario McMaster pain, and WOMAC function scores were recorded. Serum and synovial fluid were measured by enzyme-linked immunosorbent assays for inflammatory cytokines, bradykinin, and leptin. In 20 subjects, terminal heavy water ingestion was used for spectral analyses of serum and joint fluid samples. There were statistically significant improvements in pain and function. Both serum and synovial fluid samples showed significant decreases for a majority of inflammatory cytokines, leptin, and bradykinin in the oral hyaluronic acid preparation group. Heavy water analyses revealed a significant decrease in hyaluronic acid turnover in the synovial fluid of the treatment group. A preparation containing hyaluronic acid and other glycosaminoglycans holds promise for a safe and effective agent for the treatment for patients with knee osteoarthritis and who are overweight. Further studies will be required to see whether this is a disease-modifying agent.